Radio Programme on how to Increase Harvests through Good Soil Ferlitiy Management - Mubiru, Wasswa (Technical Centre for Agricultural and Rural Cooperation, 2008)
Good soil fertility management ensures that the soil can actually provide the nutrients in sufficient amounts at all times during the growth of plants. Soil fertility in many parts of Africa, however, is declining. Africa?s consumption of fertilizers is the lowest in the world and organic matter that could, to some extent, replace fertility, is often burnt and soils left bare to the degrading effects of the sun and the wind. How can farmers increase their harvests when their soils are poor?